Myth of Masculinity in Novels Seperti Dendam, Rindu Harus Dibayar Tuntas by Eka Kurniawan - Afifah Fitri Wahyuningtyas; Karkono (Universitas Negeri Semarang, 2025)
This research aims to investigate the myth of masculinity in novels such as Dendam, Rindu Harus Dibayar Tuntas, and its influence on the characters' personalities, as well as the implications of the characters' personalities formed by the myth of masculinity on the conflict in the novel. This research employs a qualitative approach, utilizing a literature study and document study method. This study employs Roland Barthes' theory of semiotics to analyze myths in novels, John Beynon's theory of masculinity to categorize the myth of masculinity in novels, and Sigmund Freud's theory of personality structure to examine the impact of the myth of masculinity on the character's personality. Furthermore, conflict theory in literary works is used to analyze the implications of the myth of masculinity on conflict in novels. The results of the study reveal that the novel encompasses six aspects of masculinity that influence the id, ego, and superego. Such personality structures trigger internal and external conflicts. Based on the analysis results, it is concluded that Uttas untangles the myth of masculinity in the novel Seperti Dendam, Rindu Harus Dibayar, examining its psychological, social, and political aspects. This novel also addresses the issue of toxic masculinity, a topic that deserves attention and action in society. Such complexity is evident in the novel Seperti Dendam, Rindu Harus Dibayar Tuntas. It is a work that can serve as inspiration and a means of human reflection on community issues that have been considered ordinary and commonplace, prompting a re-examination of their relevance to the current situation.